Cruise : the national magazine of gay travel and entertainment. (Atlanta : The Cruise Division of Cavco, 1979)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : 572 Armour Circle NE, Atlanta, GA 30324
Engels
Periodiek